Comparison of the Effectiveness of Three Methods of Recanalization in a Model of the Middle Cerebral Artery: Thrombus Aspiration via a 4F Catheter, Thrombus Aspiration via the GP Thromboaspiration Device, and Mechanical Thrombectomy Using the Solitaire Thrombectomy Device - Christopher Tennuci; Gillian Pearce; Julian Wong; Sanjeev Nayak; Tom Jones; Frank Lally; Christine Roffe (Stroke Research and Treatment)
Introduction. This paper compares different approaches to recanalization in a model of the middle cerebral artery (MCA). Methods. An occlusive thrombus (lamb's blood) was introduced into the MCA of a model of the cerebral circulation perfused with Hartmann's solution (80 pulsations/min, mean pressure 90 mm Hg). Three methods of clot retrieval were tested: thrombus aspiration via a 4F catheter (n=26), thrombus aspiration via the GP thrombus aspiration device (GPTAD) (n=30), and mechanical thrombectomy via the Solitaire Device (n=30). Results. Recanalization rate was similar for all 3 approaches (62%, 77%, and 85%). Time to recanalization was faster with aspiration devices (41 SD 42 s for 4F and 61 SD 21 s for GPTAD) than with the Solitaire (197 SD 64 s P<.05 Kruksal-Wallis). Clot fragmentation was the same in the Solitaire (23%) and the GPTAD (23%), but higher with the 4F (53%, P<.05). Conclusion. In this model, thrombus aspiration was faster than mechanical thrombectomy, and similarly effective at recanalization. These results should be confirmed in vivo.